2022
DOI: 10.1186/s13062-022-00344-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Synj2bp in mouse liver regulates the extent of wrappER-mitochondria contact to maintain hepatic lipid homeostasis

Abstract: Background In mouse liver hepatocytes, nearly half of the surface area of every mitochondrion is covered by wrappER, a wrapping-type of ER that is rich in fatty acids and synthesizes lipoproteins (VLDL) (Anastasia et al. in Cell Rep 34:108873, 2021; Hurtley in Science (80- ) 372:142–143, 2021; Ilacqua et al. in J Cell Sci 135:1–11, 2021). A disruption of the ultrastructure of the wrappER-mitochondria contact results in altered fatty acid flux, leading to hepatic dyslipidemia (Anastasia et al. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…In contrast, SYNJ2BP KO led to a reduction in the number of PLA foci per cell, indicating a decrease number of MERCs ( Fig 7I and J ). Together these results confirm that the quantity of MERCs is proportional to the level of SYNJ2BP expression ( Ilacqua et al, 2022 ; Pourshafie et al, 2022 ), which therefore strongly influences mitochondrial Ca 2+ uptake capacity.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…In contrast, SYNJ2BP KO led to a reduction in the number of PLA foci per cell, indicating a decrease number of MERCs ( Fig 7I and J ). Together these results confirm that the quantity of MERCs is proportional to the level of SYNJ2BP expression ( Ilacqua et al, 2022 ; Pourshafie et al, 2022 ), which therefore strongly influences mitochondrial Ca 2+ uptake capacity.…”
Section: Resultssupporting
confidence: 73%
“…Quantitative analysis, using confocal microscopy to compare control, SYNJ2BP KO, and SYNJ2BP overexpressing fibroblasts, demonstrated that the presence of ESYT1 at mitochondria is dependent on SYNJ2BP expression ( Fig 3C ). In contrast to SYNJ2BP overexpression, loss of SYNJ2BP which decreased MERCs ( Ilacqua et al, 2022 ; Pourshafie et al, 2022 ) was associated with a decreased localization of ESYT1 at mitochondria.…”
Section: Resultsmentioning
confidence: 73%
“…In addition, while MAM contacts ER “loosely” (gap distance of ≥10 nm), liver mitochondria are also contacted by tightly-adhering ER (“wrappER”) that is distinct from MAM [ 340 ], with essentially no gaps between the two organelles. WrappER mediates the biogenesis of lipids and lipoproteins [ 341 ] and plays an important role in cholesterol synthesis and trafficking via three-way ER-mitochondria-peroxisome contacts [ 342 ]. Taken together, these results are not only consistent with the concept that AD is indeed a lipid disorder, but also imply that in the context of AD pathology, the C99-cholesterol axis may not be confined to the brain.…”
Section: Tissue Specificitymentioning
confidence: 99%
“…Qualitatively, we found that wrappER exists in both 3-month and 2-year murine liver tissue (Figures 3G'-H'), but in 3-month tissue wrappER contact is much more extensive (Figures 3G"-H"). This suggests that liver lipid homeostasis may be negatively impacted (63)(64)(65). However, to confirm these changes and further explore the implications of these mitochondrial morphological alterations, we analyzed metabolism and performed lipidomics in mice.…”
Section: Ultrastructural Changes In Murine Liver Reveals Aging Is Ass...mentioning
confidence: 99%